Geochemical and VOC-constraints on landfill gas age and attenuation characteristics: A case study from a waste disposal facility in Southern California. (July 2016) - Hagedorn, Benjamin; Kerfoot, Henry B.; Verwiel, Mark; Matlock, Bruce
Highlights: Quantification of landfill gas and natural gas methane impact at perimeter probes. Method to assess the timing of landfill gas releases. Documentation of natural attenuation based on time-series VOC patterns. Abstract: In this study, a multi-tracer approach was applied to a complex, methane-impacted site in Southern California to (1) distinguish between natural gas and landfill gas (LFG)-derived methane impacts at site perimeter gas probes, (2) estimate the relative age of the LFG at these probes, and (3) document natural attenuation trends during a 3-year monitoring period. Relationships between methane and ethane values suggest that at the majority of probes, methane is from LFG and not from natural gas and that the relative contribution of LFG methane at these probes has increased over the monitoring period. To evaluate whether LFG is attenuating in the subsurface, the relative age of LFG was estimated by comparing readily degraded VOCs that are major constituents in LFG (toluene in this case) with those resistant to degradation (Freons). Time-series data trends are consistent with several probes being impacted by fresh LFG from recent releases that occurred after the update of the local LFG collection and control system (LFGCCS). Data further indicate some probes to be only affected by legacy LFG from a past release that occurred prior to the LFGCCS update and that, because of a lack of oxygen in the subsurface, had not been fully degraded. The outlined attenuation evaluation methodology is potentially applicable to other sites or even groundwater contaminants; however, the assessment is limited by the degree of homogeneity of the LFG source composition and non-LFG-derived toluene inputs to the analyzed samples.